Switching Intent of Disruptive Green Products: The Roles of Comparative Economic Value and Green Trust - Lin, Chunpei; Lai, Xiumei; Yu, Chuanpeng (Frontiers in Energy Research, 2021)
This study explores consumers’ motivations to switch to new products in the context of disruptive innovation and investigates the role of comparative economic value and green trust. Switching from an existing product to a disruptive green product not only involves benefits but also requires major sacrifices, which are not encountered in the context of continuous innovation. In this study, the relationships between comparative economic value, green trust, self-accountability, and disruptive green product switching intent are examined. Data were collected from China with self-administered questionnaires regarding the disruptive green product. Results of a structural model reveal positive relationships between comparative economic value, green trust, and disruptive green product switching intent. In addition, green trust mediates the effects of the comparative economic value on the disruptive green product switching intent, and self-accountability moderates the relationship between green trust and disruptive green product switching intent. From a practitioner perspective, the research is important because it illuminates the consumer’s motivations regarding product switching in the hitherto unexplored field of automobiles, for which we have shown that our extended model yields meaningful results.